A Mendelian randomization study for drug repurposing reveals bezafibrate and fenofibric acid as potential osteoporosis treatments - Li, Xiao-Hua; Pang, Wei-Wei; Zhang, Yue; Liu, Dan-Yang; Yi, Qiao-Rong; Wang, Ning; Zhang, Fu-Rong; Deng, Yun; Chen, Xiang-Ding; Greenbaum, Jonathan; Xiao, Hong-Mei; Deng, Hong-Wen; et al. (Frontiers in Pharmacology, 2023)
Lipid pathways have been implicated in the pathogenesis of osteoporosis (OP). Lipidlowering drugs may be used to prevent and treat OP. However, the causal interpretation of results from traditional observational designs is controversial by confounding. We aimed to investigate the causal association between genetically proxied lipid-lowering drugs and OP risk.We conducted two-step Mendelian randomization (MR) analyses to investigate the causal association of genetically proxied lipid-lowering drugs on the risk of OP. The first step MR was used to estimate the associations of drug target genes expression with low-density lipoprotein cholesterol (LDL-C) levels. The significant SNPs in the first step MR were used as instrumental variables in the second step MR to estimate the associations of LDL-C levels with forearm bone mineral density (FA-BMD), femoral neck BMD (FN-BMD), lumbar spine BMD (LS-BMD) and fracture. The significant lipid-lowering drugs after MR analyses were further evaluated for their effects on bone mineralization using a dexamethasone-induced OP zebrafish model.The first step MR analysis found that the higher expression of four genes (HMGCR, NPC1L1, PCSK9 and PPARG) was significantly associated with a lower LDL-C level.The genetically decreased LDL-C level mediated by the PPARG was significantly associated with increased FN-BMD (BETA = -1.38, P = 0.001) and LS-BMD (BETA = -2.07, P = 3.35×10 -5 ) and was marginally significantly associated with FA-BMD (BETA =-2.36, P = 0.008) and reduced fracture risk (OR = 3.47, P =0.008).Bezafibrate (BZF) and Fenofibric acid (FA) act as PPARG agonists. Therefore genetically proxied BZF and FA had significant protective effects on OP. The dexamethasone-induced OP zebrafish treated with BZF and FA showed increased bone mineralization area and integrated optical density (IOD) with alizarin red staining.The present study provided evidence that BZF and FA can increase BMD, suggesting their potential effects in preventing and treating OP. These findings potentially pave the way for future studies that may allow personalized selection of lipid-lowering drugs for those at risk of OP.